Changes of kinematics during underwater undulatory swimming with increasing swimming velocity - Yamakawa, K. K.; Homoto, K.; Shimojo, H.; Sengoku, Y.; Takagi, H. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to clarify about the changes of the kinematics during underwater undulatory swimming (UUS) with increasing the swimming velocity. Eight male collegiate swimmers performed three UUS trials at the 70%, 80% and 90% velocity of their maximum effort swimming velocity in a water flume. For motion analysis, a motion capture system was used to collect the three-dimensional coordinates. Using the collected coordinates, the kinematic parameters were analyzed in each trial. As the main results, the kick frequnecy increased and the relative duration of the un-propusive phase with hip extension and knee felxion decreased with increasing swimming velocity. Furtheremore, since the peak hip external roation velocity increased with increasing swimming velocity, it was considered that the hip external rotation velocity during the downward kicking related to controll the swimming velocity during underwater undulatory swimming.